EARLY PREDICTABILITY OF VIROLOGICAL RESPONSE IN PATIENTS OF CHRONIC HEPATITIS-C WITH GENOTYPE-3, TREATED WITH PEGYLATED INTERFERON AND RIBAVIRIN - Umar, Mohammad; Khaar, Hamamat-ul- Bushra; Khan, Sameera Abbas; Ahmed, Masood; Ambreen, Saima; Minhas, Zahid Mahmood; Nazar, Madeeha (Journal of Ayub Medical College Abbottabad, 2014)
Background: This study was conducted to assess the early predictability of virological response in chronic hepatitis-C patients (Genotype-3), treated with pegylated interferon alpha-2a and ribavirin with an objective of determining predictive values of Rapid Virological Response (RVR) and Early Virological Response (ETR) on Sustained Virological Response (SVR). Method: This cross sectional study was conducted in January 2014, at Holy Family Hospital, Rawalpindi by inclusion of 582 patients of chronic hepatitis being treated with Pegylated Interferon Î± 2b and ribavirin. Based on Polymerase Chain Reaction (PCR) for HCV RNA Qualitative on 4th, 12th and 24th week of treatment regimen, RVR, EVR and End treatment Response (ETR) was assessed respectively whereas 24th week post treatment PCR concluded as SVR. Effect of treatment was determined as proportions for responses in total and then compared for treatment naÃ¯ve, responders and relapsers to previous conventional therapy using Chi square test. Positive and Negative Predictive Values were also calculated. Results: Qualitative PCR for HCV revealed that 281 (69.2%) achieved RVR where 60.3% attained SVR. PPV and NPV of RVR in study population were 67.41% and 44.45% respectively and 66.29% and 57.14% respectively for EVR. Statistically significant differences in RVR, EVR and ETR were observed in patients based on conventional treatment response. Conclusion: Attainment of RVR is a prospect to categorize patients appropriate for abridged treatment and this study supported the evidence that failure to achieve EVR was congruent with failure to achieve SVR. Keywords: Hepatitis-C Virus, Rapid Virologic Response, Early Virologic Response, Positive Predictive Value, Negative Predictive Value, Pegylated Interferon, Ribavirin, conventional Interferon treatment naive, relapsers, non-repsonders